Comparison of Dispute Resolution Through Mediation in Indonesia and Japan - Sapta Eka Yanto; Zainal Arifin Hosein (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to compare the mediation systems in Indonesia and Japan, focusing on procedural differences and similarities, as well as the factors influencing their implementation in both countries. Mediation as an alternative dispute resolution offers a more peaceful and efficient solution, reducing the burden on courts. In Indonesia, mediation is regulated by the Supreme Court Regulation (PERMA) No. 1 of 2016, which mandates that mediation be conducted at the early stages of the trial with non-judge mediators. In contrast, Japan's wakai system allows mediation to occur at various stages of the judicial process with judges serving as mediators. Additional differences include the procedures for conducting mediation, the authority of mediators, and the mechanisms for ratifying mediation results that hold the force of law in both countries. Despite the fundamental differences in their systems, both countries share the same goal of achieving a fair resolution beneficial to both parties. Cultural factors, legal systems, and court structures are essential elements influencing these differences and similarities. This research provides important insights for the development of mediation practices in Indonesia by considering the implementation of a more flexible system similar to Japan’s.